Implementasi Program Jumat Mubarak Untuk Meningkatkat Akhlak Peserta Didik Di Sekolah Dasar - Nuriman, Restu; Darmiyanti, Astuti; Fahmi, Yadi (Universitas Majalengka, 2025)
In recent years, there has been a decline in the moral quality of students in various educational institutions, this can be seen from the increase in bullying cases in 2023. The Federation of Indonesian Teachers' Unions (FSGI) provides data that in 2023, especially in January - September, there will be 30 cases of bullying, where in 2023 there will be an increase in bullying cases from 2022. Of the 30 cases, there were 2 victims who died. With the above problems, we can know that there is a decline in the quality of morals in students. The Friday Mubarok program held by SDN Pangulah Baru 1 is very much in accordance with the purpose of Islamic education where the goal is to produce people who have a personality of devotion to Allah SWT and have moral karimah. The objectives of this study are: 1). To find out the Friday Mubarok program at SDN Pangulah Baru 1, 2). To find out the supporting and inhibiting factors of the implementation of the Friday Mubarak Program, 3). To find out the impact of the Friday Mubarok Program on the morals of students. In this study, the researcher used a descriptive research method. The descriptive research method is one of the methods that has the purpose of describing, explaining and being able to answer several problems about events that are happening. The results of the research were obtained that the Friday Mubarak Program has an important role in fostering and creating moral character in students. The activities carried out during this Friday Mubarak activity are performing dhuha prayers, the recitation of prayers and asmaul husna, and the existence of a cult of pie teachers as the coordinator of the Friday Mubarak Program.